2018
DOI: 10.3389/fmars.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Holobiont Diversity in a Reef-Building Coral over Its Entire Depth Range in the Mesophotic Zone

Abstract: Mesophotic reef-building coral communities (∼30-120 m depth) remain largely unexplored, despite representing roughly three-quarters of the overall depth range at which tropical coral reef ecosystems occur. Although many coral species are restricted to shallow depths, several species occur across large depth ranges, including lower mesophotic depths. Yet, it remains unclear how such species can persist under extreme low-light conditions and how the different symbiotic partners associated with these corals contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 83 publications
4
43
0
Order By: Relevance
“…Mesophotic Coral Ecosystems (MCEs), located between 30 and >150 m of water depth, may act as a refuge of coral populations due to favorable conditions in this less altered environment (Bongaerts et al, 2010). Particularly, in our study area, San Andres Island, populations of corals reaching the lower (>60 m) mesophotic zone, 40-90 m, such as Agaricia undata exhibit genetic connectivity throughout its depth range (Gonzalez-Zapata et al, 2018a), supporting this zone as a major reefbuilding coral refuge. It has been suggested that depending on the type of endosymbiont, corals can acclimatize to deeper depths (Ziegler et al, 2015), which was in fact observed in the bacterial population from A. undata in San Andrés Island (Gonzalez-Zapata et al, 2018a).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Mesophotic Coral Ecosystems (MCEs), located between 30 and >150 m of water depth, may act as a refuge of coral populations due to favorable conditions in this less altered environment (Bongaerts et al, 2010). Particularly, in our study area, San Andres Island, populations of corals reaching the lower (>60 m) mesophotic zone, 40-90 m, such as Agaricia undata exhibit genetic connectivity throughout its depth range (Gonzalez-Zapata et al, 2018a), supporting this zone as a major reefbuilding coral refuge. It has been suggested that depending on the type of endosymbiont, corals can acclimatize to deeper depths (Ziegler et al, 2015), which was in fact observed in the bacterial population from A. undata in San Andrés Island (Gonzalez-Zapata et al, 2018a).…”
Section: Introductionsupporting
confidence: 53%
“…Particularly, in our study area, San Andres Island, populations of corals reaching the lower (>60 m) mesophotic zone, 40-90 m, such as Agaricia undata exhibit genetic connectivity throughout its depth range (Gonzalez-Zapata et al, 2018a), supporting this zone as a major reefbuilding coral refuge. It has been suggested that depending on the type of endosymbiont, corals can acclimatize to deeper depths (Ziegler et al, 2015), which was in fact observed in the bacterial population from A. undata in San Andrés Island (Gonzalez-Zapata et al, 2018a). In addition, many species of fish, corals, and other invertebrates from shallow reefs are also found in mesophotic reefs and it is proposed that these populations could contribute to the recovery of affected populations in shallower areas following a disturbance (Kramer et al, 2019).…”
Section: Introductionmentioning
confidence: 62%
“…This rare coral patch formation composed mostly of Orbicella (instead of Acropora in the Indo-Pacific) species (O. annularis, O. faveolata and O. franksi) with some colonies attaining large sizes (Diaz et al, 1996a;Foster et al, 2013). This habitat includes a different community of benthic organisms and fish compared to the deepest, most exposed external environments of the atolls and barrier reefs of the area (Sánchez et al, 1997a;Díaz-Pulido et al, 2004;Velásquez and Sánchez, 2015;Sánchez, 2016;Gonzalez-Zapata et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research on MCEs has increased substantially over the past two decades (Kahng et al, 2010(Kahng et al, , 2014Loya et al, 2016). This is largely due to the combination of increased ease of in situ data observations and collections through underwater technological advancements (i.e., SCUBA, closed circuit rebreathers, remotely operated vehicles, and submersibles) and the appraisal of MCEs as potential refuges for adjacent altiphotic (i.e., shallow reef habitats adjacent to upper mesophotic reefs; see Baldwin et al, 2018) coral reefs (Glynn, 1996;Lesser et al, 2009;Bongaerts et al, 2010;Hinderstein et al, 2010). As deep-water refuges, MCEs may provide a haven for scleractinian corals and commercially important fish (Lindfield et al, 2016), thereby replenishing adjacent impacted shallow water reefs with both coral (Bongaerts et al, 2017;Kahng et al, 2017) and fish larvae (Bejarano et al, 2014;Vaz et al, 2016), leading to the formation of the deep reef refuge hypothesis (Bongaerts et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more attention has been given to MCEs in the Atlantic and Caribbean region, including research off Puerto Rico (Galindo-Estronza et al, 2016;Veglia et al, 2018), the US Virgin Islands (Holstein et al, 2016;Weinstein et al, 2016), Curaçao (Hoeksema et al, 2016;Glasl et al, 2017), Bermuda (Goodbody-Gringley et al, 2015), Honduras (Laverick et al, 2017), Belize (Lesser and Slattery, 2013), the Bahamas (Slattery and Lesser, 2012;Slattery et al, 2016), Little Cayman (Brazeau et al, 2013), Colombia (Gonzalez-Zapata et al, 2018), and Mexico (Gress et al, 2017). In Puerto Rico, the primary focus of past (e.g., Starck and Colin, 1978;Nelson and Appeldoorn, 1985;Dennis et al, 2004) and more recent work (Sherman et al, 2010(Sherman et al, , 2013a has been on MCEs located off the south coast of the island (see review by Appeldoorn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%